Water budget in flat vs. steep subduction: implication for volcanism and potential for H2 production - Gauthier Alexis; Larvet Tiphaine; Le Pourhiet Laetitia; Moretti Isabelle (BSGF - Earth Sciences Bulletin)
In this study, we model the processes of (de)hydration and melting within subduction zones using a thermo-mechanical modeling approach. Multiple 2D simulations are conducted to investigate how the subduction angle influences the water budget in oceanic-continental subduction, focusing mainly on the variation of slab dip angle along the strike of the Andes. It appears that in the case of flat subduction, the mantle hydration zone is large, extending up to 500 km from the trench. This extent depends on the length of flat slab segment which, in turn, depends on the velocity of the overriding plate. In the case of a steep subduction, the zone is narrower, and is located between the trench and the volcanic arc. Magma formation competes with hydration of the mantle wedge for the use of water expelled from the subducting plate. In the transition from a steep to a flat slab, the mantle hydration zone widens and the volcanic zone moves away from the trench. The oceanic crust may undergo melting, leading to a change in magma composition and the development of adakitic volcanism, before volcanism diminishes in intensity and then disappears. Our study provides geodynamic insights into observations related to volcanism in the Pampean flat slab in South America. Using the quantification of water involved in mantle wedge hydration as a proxy for H2 production, we propose that flat subductions are the most promising areas for H2 exploration. Additionally, deep H2 production appears to be particularly sensitive to the amount of subducted sediments, regardless of whether subduction is flat or steep. Lower plate serpentinization does not affect deep H2 production.